Cytotoxicity Measurements of CdSe and Ag Hybrid Nano Composites for In-vitro Bioimaging Applications - Neeraj Rathee; Neena Jaggi (New Trends in Physical Science Research Vol. 4, 2022)
Silver metal has been known for its excellent anti-microbial activities. With the interaction of these metal nanoparticles with human cells, a hint of safety emerges. In this present work we have synthesised a hybrid nanocomposites of Ag with Cadmium Selenide (CdSe) Quantum Dots (QDs) for their cytotoxicity measurements. Due to the high luminescent properties of CdSe QDs these hybrid nanostructures can be used in medical detection and treatments. Morphological studies of CdSe QDs and Ag composites with CdSe were done using TEM. It was revealed from the TEM image that; Ag formed a coating layer over the surface QDs. Cytotoxicity of CdSe based QDs were measured on HEK293 cell line using MTT assay. It was found from the measurements that QDs were less toxic even at higher concentration on 1000nM for 24 hours. When toxicity levels of both the samples were compared it was found that the hybrid nanocomposites of Ag with CdSe were non-toxic than CdSe QDs. The morphology of HEK293 cell line was continuous evaluated using an optical microscope. With these advantages of less toxicity the composites of CdSe QDs with Ag can be used in various biological imaging technique and other medical detection and treatments.